Fecal sST2 correlates with the disease severity of ulcerative colitis - Jovanovic, Marina; Gajovic, Nevena; Jurisevic, Milena; Simovic Markovic, Bojana; Maric, Veljko; Jovanovic, Milan; Arsenijevic, Nebojsa; Zdravkovic, Natasa (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Ulcerative colitis (UC) is a chronic, relapsing inflammatory disease affecting the distal colon and rectum with complex pathogenesis and diagnosis, indicating the need for new diagnostic and prognostic markers. The aim of this study was to determine the fecal values of TNF-α, IL-17, IL-10 and soluble protein ST2 (sST2) in the patients with UC and their relationship with clinicopathological aspects. Methods. The samples of stool of 80 patients with UC were analyzed. Concentrations of TNF-α, IL-17, IL-10 and sST2 were measured by ELISA. Results. Concentrations of TNF-α, IL-17 and sST2 were significantly increased in the feces of patients with the higher endoscopic, clinical and total Mayo score, as well as in the patients with an intense crypt destruction, erosion of the mucous membranes, architectural changes, neutrophil infiltration and eosinophil infiltration. The local value of anti-inflammatory cytokine IL-10 in liquid fraction of feces was increased in the patients with an advanced endoscopic stage of UC. The moderate positive correlation between the fecal sST2/IL-17 and the clinical and histological parameters of disease severity and also the strong correlation between sST2 and IL-17 was also observed in the feces of patients with UC. The analysis of receiver operating characteristic (ROC) curves showed that the optimal cut-off value for sST2 of 624.0 pg/g allows the discrimination of clinical stages of UC. Conclusion. The increased fecal value of sST2 in the UC patients with a higher endoscopic, clinical and histological stage of disease may be considered as a sign of the disease severity. The fecal values of sST2 can be used as a valuable marker for UC severity.
Keywords: colitis, ulcerative; biomarkers; disease progression; feces; tumor necrosis factor-alpha; interleukin-10; interleukin-17; il1rl1 protein, human